2018
DOI: 10.1186/s12875-018-0754-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of diagnostic tests and the appropriateness of the treatment decision in patients with suspected urinary tract infection in primary care in Denmark – observational study

Abstract: BackgroundInappropriate prescription of antibiotics is the leading driver of antimicrobial resistance (AMR). The majority of antibiotics are prescribed in primary care.Understanding how general practitioners (GPs) use diagnostic tests and the effect on treatment decision under daily practice conditions is important to reduce inappropriate prescription of antibiotics. The aim of the study was to investigate the use of diagnostic tests in primary care patients with suspected urinary tract infection (UTI) and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…As hypothesised, our study showed an even lower number of correctly ordered cultures of one out of ten patients [4,8,23]. This is far below the one out of three that was found in an earlier study during office hours [4].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…As hypothesised, our study showed an even lower number of correctly ordered cultures of one out of ten patients [4,8,23]. This is far below the one out of three that was found in an earlier study during office hours [4].…”
Section: Discussioncontrasting
confidence: 62%
“…One can assume that with acute onset of symptoms, and daytime GP practices only open during at best 30% of the 168 h in a week, a large proportion of UTI management happens at the out-of-hours care [20]. Earlier studies on UTI diagnostics have only focused on appropriateness of current diagnostic tests during daytime practice [4,8,20]. None of these studies analysed the diagnostic process of UTIs during out-of-hours care.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review from 2010 found that using urine microscopy as an add-on to urine dipstick slightly improved the sensitivity [6]. However, this combination still seems to be inferior to urine culture in order to avoid over-diagnosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…One of the few countries with the wide availability of rapid tests is Denmark. This scenario allowed us to assess the use of diagnostic tools in daily practice and its effect on treatment decision in patients with suspected urinary tract infection (UTI) 25. We found that in 85% of the patients with a suspected uncomplicated UTI, urine culture was part of the diagnostic process.…”
Section: Overdiagnosis Versus ‘Too Much Medicine’mentioning
confidence: 99%